Mechanical relaxation and freezing in the room temperature strain glass alloy Ti50(Pd40Cr10). (1st August 2018) - Zhou, Yumei; Wang, Yu; Xue, Dezhen; Ding, Xiangdong; Sun, Jun; Ren, Xiaobing; Lookman, Turab
Abstract: The alloy Ti50 (Pd40 Cr10 ) undergoes a strain glass transition around room temperature evidenced by frequency dispersion of dynamic mechanical properties and lack of average structure change from that of the high symmetry austenite phase. However, since the strain glass transition is not a thermodynamic phase transition but a dynamic freezing process governed by the kinetics, a quantitative characterization of the slowing down of dynamics during the strain glass transition is still lacking. In the present study, the probability distribution function (PDF) of the relaxation time of the strain glass alloy is investigated spanning the whole transition temperature range (253 K–313 K). The slowing down of dynamics of the strain glass is indicated by the rapid increase of the characteristic relaxation time ( ) upon cooling. The, as a function of temperature, shows a transition from Vogel–Fulcher relationship to an Arrhenius relationship. Such a change suggests two fundamentally different states: unfrozen strain glass state and frozen strain glass state. Furthermore, the spread of the PDF is connected to the fraction of quasi-static nanodomains, which helps the understanding of the dynamic freezing process in the strain glass.